Safety Analysis of Dorsal Root Ganglion Stimulation in the Treatment of Chronic Pain. Issue 2 (12th March 2019) - Deer, Timothy; Pope, Jason; Hunter, Corey; Falowski, Steven; Kapural, Leonardo; Kramer, Jeffery; Levy, Robert
Abstract : Background: Stimulation of the dorsal root ganglion (DRG) in the treatment of chronic, intractable pain has shown excellent clinical results in multiple published studies, including a large prospective, randomized, controlled trial. Both safety and efficacy have been demonstrated utilizing this therapeutic approach for many chronic complaints. Continued assessment of neuromodulation therapies, such as DRG stimulation, are not only an important aspect of vigilant care, but are also necessary for the evaluation for safety. Materials and Methods: Safety and complaint records for DRG and spinal cord stimulation (SCS) stimulation were obtained from the manufacturer, analyzed and compiled to further assess ongoing device safety. Complaint event data were stratified according to complain type as well as overall rates. Data from similar time periods were compared between epidural neurostimulation devices by the same manufacturer as well as rates reported in the literature. Results: Overall, DRG stimulation device event rates were lower or comparable to similar epidurally placed neurostimulation devices. Rates of events varied from 0 to 1.0% for DRG stimulation ( n >500+ implants) which was similar to the event rate for SCS by the same manufacturer ( n >2000+ implants). In comparison, complaints and adverse events ranged from 0 to 14% for SCS in the literature. Discussions: The current results from a large consecutive cohort obtained from manufacturer records indicates that DRG stimulation demonstrates an excellent safety profile. Reported event rates are similar to previously reported adverse event and complaint rates in the literature for this therapy. Similarly, safety events rates were lower or similar to previously reported rates for SCS, further demonstrating the comparative safety of this neuromodulation technique for chronic pain treatment.